School finance centralization and revenue levels: Evidence from a school finance reform - Jinsub Choi (Journal of Applied Economics, 2023)
This paper studies whether the centralization of public school finance affects school revenue levels. The theoretical framework indicates that centralization has price and income effects on the pivotal voter's demand for school revenue, but the overall effect is ambiguous. A public school finance reform in Michigan (U.S. state), which centralized its school finance system by restricting local discretion on school revenue, provides a good policy variation for a quasi-experimental design. Using district-level panel data on school finance in Michigan and neighboring states over the fiscal-year period of 1990-2004, I find that the reform has a negative effect on revenue levels. The sixth year after the reform and onwards, the reform reduces per-pupil revenue by 1,300 on average. The reform reduces revenue levels in both low- and high-revenue districts, but the higher-revenue districts tend to sustain more pronounced reductions.
Keywords: 330; School finance centralization; school finance equalization; school revenue levels